Characterization of arsenic resistant plant‐growth promoting indigenous soil bacteria isolated from Center‐East regions of India. (18th June 2019) - Pandey, Neha; Keshavkant, S.
Abstract: A total of 45 morphologically distinct arsenic (As)‐resistant bacterial strains were isolated from the soils of different regions of Chhattisgarh, India. The minimum inhibitory concentration (MIC) values of these isolates varied widely in the range of 100‐500 mM for arsenate [As(V)] and 15‐30 mM for arsenite [As(III)]. Out of forty‐five, three isolates viz; ARP3, ARRP3, and ADT5 also revealed plant growth‐promoting properties, including phosphate solubilization and production of siderophores, indoleacetic acid, ammonia, and exopolysaccharide. Besides all these, the strains not only exhibited significant growth in the presence of As(V)/As(III) but also displayed higher efficiency (87%‐94%) of As removal from the growth medium followed by intracellular accumulation (17‐19 mg As/g). Hydride generation atomic absorption spectroscopic (HG‐AAS) analysis revealed the intracellular accumulation of As, and the structural changes that took place in these isolates were further confirmed by microscopic studies. The 16 S rRNA and phylogenetic analyses unveiled that the isolates ARP3, ARRP3, and ADT5 belonged to genera Pseudomonas, Exiguobaterium, and Microbacterium, respectively. The conducted study suggested that such beneficial bacterial strains could be conveniently exploited at a commercial level for enhancing plant growth in As‐contaminated agricultural fields, thereby improved productivity and enhanced bioremediation of soil having alarming strength of As.